3D Reconstruction & Modeling of the Traditional Greek Trechadiri: “Aghia Varvara” - Andreas Arapakopoulos; Orestis Liaskos; Sofia Mitsigkola; Georgios Papatzanakis; Sofia Peppa; Georgios Remoundos; Alexandros Ginnis; Christos Papadopoulos; Dimitrios Mazis; Odysseas Tsilikidis; Yannis Yighourtakis (Heritage, 2022)
3D modeling techniques have grown increasingly prevalent in a variety of disciplines, including cultural heritage and ship design. The methodology used in the 3D reconstruction of a traditional Greek boat with the Trechadiri hull type named “Aghia Varvara” is presented in this study. The original boat was built in 1925 and is characterized as a modern cultural heritage monument by the Greek Ministry of Culture. The digital reconstruction of the boat is explained in detail, including 3D laser scanning and computer aided geometric design (CAGD), as well as the description of the 3D printing process. The boat’s 3D digital model has been used for the enrichment of the NAVS Project’s digital library, demonstrating the unique geometrical, typological, and cultural characteristics of Greek traditional shipbuilding, a living craft which listed on Greece’s National Inventory of Intangible Cultural Heritage.